Activation of PKA, p38 MAPK and ERK1/2 by gonadotropins in cumulus cells is critical for induction of EGF-like factor and TACE/ADAM17 gene expression during in vitro maturation of porcine COCs - Yamashita Yasuhisa; Hishinuma Mitsugu; Shimada Masayuki (BMC, 2009)
Abstract Objectives During ovulation, it has been shown that LH stimulus induces the expression of numerous genes via PKA, p38 MAPK, PI3K and ERK1/2 in cumulus cells and granulosa cells. Our recent study showed that EGF-like factor and its protease (TACE/ADAM17) are required for the activation of EGF receptor (EGFR), cumulus expansion and oocyte maturation of porcine cumulus-oocyte complexes (COCs). In the present study, we investigated which signaling pathways are involved in the gene expression of EGF-like factor and in Tace/Adam17 expression in cumulus cells of porcine COC during in vitro maturation. Methods Areg, Ereg, Tace/Adam17, Has2, Tnfaip6 and Ptgs2 mRNA expressions were detected in cumulus cells of porcine COCs by RT-PCR. Protein level of ERK1/2 phosphorylation in cultured cumulus cells was analyzed by westernblotting. COCs were visualized using a phase-contrast microscope. Results When COCs were cultured with FSH and LH up to 2.5 h, Areg, Ereg and Tace/Adam17 mRNA were expressed in cumulus cells of COCs. Areg, Ereg and Tace/Adam17 gene expressions were not suppressed by PI3K inhibitor (LY294002), whereas PKA inhibitor (H89), p38 MAPK inhibitor (SB203580) and MEK inhibitor (U0126) significantly suppressed these gene expressions. Phosphorylation of ERK1/2, and the gene expression of Has2, Tnfaip6 and Ptgs2 were also suppressed by H89, SB203580 and U0126, however, these negative effects were overcome by the addition of EGF to the medium, but not in the U0126 treatment group. Conclusion The results showed that PKA, p38 MAPK and ERK1/2 positively controlled the expression of EGF-like factor and TACE/ADMA17, the latter of which impacts the cumulus expansion and oocyte maturation of porcine COCs via the EGFR-ERK1/2 pathway in cumulus cells.